Biomimetic Self‐Healing. Issue 36 (21st July 2015) - Diesendruck, Charles E.; Sottos, Nancy R.; Moore, Jeffrey S.; White, Scott R.
Abstract Self‐healing is a natural process common to all living organisms which provides increased longevity and the ability to adapt to changes in the environment. Inspired by this fitness‐enhancing functionality, which was tuned by billions of years of evolution, scientists and engineers have been incorporating self‐healing capabilities into synthetic materials. By mimicking mechanically triggered chemistry as well as the storage and delivery of liquid reagents, new materials have been developed with extended longevity that are capable of restoring mechanical integrity and additional functions after being damaged. This Review describes the fundamental steps in this new field of science, which combines chemistry, physics, materials science, and mechanical engineering.